The Role of Extracellular Loops in the Folding of Outer Membrane Protein X (OmpX) of Escherichia coli - Hermansen, Simen; Ryoo, David; Orwick-Rydmark, Marcella; Saragliadis, Athanasios; Gumbart, James C.; Linke, Dirk (Frontiers in Molecular Biosciences, 2022)
The outer membrane of Gram-negative bacteria acts as an additional diffusion barrier for solutes and nutrients. It is perforated by outer membrane proteins (OMPs) that function most often as diffusion pores, but sometimes also as parts of larger cellular transport complexes, structural components of the cell wall, or even as enzymes. These OMPs often have large loops that protrude into the extracellular environment, which have promise for biotechnological applications and as therapeutic targets. Thus, understanding how modifications to these loops affect OMP stability and folding is critical for their efficient application. In this work, the small outer membrane protein OmpX was used as a model system to quantify the effects of loop insertions on OMP folding and stability. The insertions were varied according to both hydrophobicity and size, and their effects were determined by assaying folding into detergent micelles in vitro by SDS-PAGE and in vivo by isolating the outer membrane of cells expressing the constructs. The different insertions were also examined in molecular dynamics simulations to resolve how they affect OmpX dynamics in its native outer membrane. The results indicate that folding of OMPs is affected by both the insert length and by its hydrophobic character. Small insertions sometimes even improved the folding efficiency of OmpX, while large hydrophilic inserts reduced it. All the constructs that were found to fold in vitro could also do so in their native environment. One construct that could not fold in vitro was transported to the OM in vivo, but remained unfolded. Our results will help to improve the design and efficiency of recombinant OMPs used for surface display.